Analog Hardware Description Language and Its Relations to VHDL - Vlcek, K.; Popelek, J. (Radioengineering Society, 1996)
Primary motivations for analogue hardware description language (VHDL-A) is to support the modelling of physical systems. The VHDL-A must therefore allow to model the physical conservation laws, such as the energy conservation law, which states that energy can neither be created nor destroyed, but it can only change its form.
Keywords: VHDL; VHDL-A; circuit description; circuit simulation; analo; digital; mixed D/A